Photoperiods induced the circRNA differential expression in the thyroid gland of OVX+E2 ewes - Wang, Wei; He, Xiaoyun; Di, Ran; Wang, Xiangyu; Chu, Mingxing (Frontiers in Endocrinology, 2022)
Circular RNAs (circRNAs) are non-coding RNAs newly identified and play important roles in RNA regulation. However, little is known regarding photoperiods induced circRNAs in the thyroid gland. In this study, we performed a comprehensive analysis of circRNA profiles in the thyroid gland of OVX+E2 ewes at different photoperiods by whole transcriptome sequencing. A total of 37,470 novel circRNAs were detected in different photoperiods (42 days of short photoperiod treatment, SP42; 42 days of long photoperiod treatment, LP42; SP42 transfer to LP42, SPLP42), with a total of 817 circRNAs for SP42-LP42 (down: 132; up: 114), LP42-SPLP42 (down: 136; up: 112) and SP42-SPLP42 (down: 182; up: 141) having differentially expressed. Functional enrichment annotation analysis of DE-circRNAs for GO and KEGG by R package, features that influence photoperiod response in Sunite ewes through the Inositol phosphate metabolism, cGMP-PKG signaling pathway, Calcium signaling pathway, MAPK signaling pathway, and Oocyte meiosis. In addition, competitive endogenous RNA (ceRNA) network analysis revealed target binding sites for identified miRNAs in DE-cirRNAs such as oar-miR-10b, oar-miR-200c, oar-miR-21, oar-miR-370-3p, oar-miR-377-3p, oar-miR-181a, oar-miR-432, and oar-miR-495-3p. These results of this study will provide some new information for understanding circRNA function as well as the changes in the sheep thyroid gland under different photoperiods.